PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK TERHADAP MINAT MEMBACA PADA PESERTA DIDIK KELAS II DI SEKOLAH DASAR NEGERI 09 TANJUNG BARAT - Junita Nurfazriah Putri; Dewi Setiyaningsih; Siska Kusumawardani; Lutfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low interest in reading among students. This research uses the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted in class II of SD Negeri 09 Tanjung Barat. The data collection technique in this study went through two stages, namely expert validation tests and practicality tests. The results of this study indicate that the learning media that has been made in the form of a scrapbook is said to be valid from the results of the calculations of media experts who obtained an assessment of 81%, language experts obtained an assessment of 100%, and material experts obtained an assessment of 98% with very valid criteria. The results of the practicality test of educator responses were 98% and student responses obtained an assessment of 90% with very practical criteria. Thus, it can be concluded that the scrapbook learning media is very valid and very practical to be applied to learning in class II with an average of 93.4%.